The Activation of Mesenchymal Stem Cells by Glioblastoma Microvesicles Alters Their Exosomal Secretion of miR-100-5p, miR-9-5p and let-7d-5p - Delphine Garnier; Edward Ratcliffe; Joséphine Briand; Pierre-François Cartron; Lisa Oliver; François M. Vallette (Biomedicines, 2022)
Glioblastoma (GBM) is the most aggressive brain tumor, and despite initial response to chemo- and radio-therapy, the persistence of glioblastoma stem cells (GSCs) unfortunately always results in tumor recurrence. It is now largely admitted that tumor cells recruit normal cells, including mesenchymal stem cells (MSCs), and components of their environment, to participate in tumor progression, building up what is called the tumor microenvironment (TME). While growth factors and cytokines constitute essential messengers to pass on signals between tumor and TME, recent uncovering of extracellular vesicles (EVs), composed of microvesicles (MVs) and exosomes, opened new perspectives to define the modalities of this communication. In the GBM context particularly, we investigated what could be the nature of the EV exchange between GSCs and MSCs. We show that GSCs MVs can activate MSCs into cancer-associated fibroblasts (CAFs)-like cells, that subsequently increase their secretion of exosomes. Moreover, a significant decrease in anti-tumoral miR-100-5p, miR-9-5p and let-7d-5p was observed in these exosomes. This clearly suggests a miRNA-mediated GBM tumor promotion by MSCs exosomes, after their activation by GBM MVs.